The Inexplicit Stipulations of the Validity and Reliability of the Condition in the Civil Code - Reza Maghsoudi; Sayyed Mostafa Muhaghigh Damad; Sayyed Mahdi Allameh; Ali Reza Mazlum Rahni; Hormuz Asadi Koohbad (آموزه‌‌های فقه مدني)
Article 190 of the Civil Code of Iran about the basic provisions of the validity of transactions and about agreements has been independent and primary (principal) and the legislation has not asseverated about the transmission of these provisions to the conditions stipulated within the contract. The silence of the civil code about the inclusion of the article 190 to the conditions stipulated in the contract has leaded disagreement between the law scholars. From the other side the articles 232 and 233 have reflected the exclusive (specific) conditions of the validity of the provisions but these conditions in respect to the present periods have not been complete and sufficient and have not been responsive to the new-found issues. The changes of the circumstances and the emergency of the fresh social phenomena, it demands the necessity of the development and review in the conditions of the validity of the stipulation. In the following note, with the analytic-descriptive method, the inclusive provisions of the validity of the stipulation with the establishment of the two ijtihadi and new conditions meaning the necessity of the compliance of the conditions with basic principles and limitations have been completed and explained. Also, in the public circumstances of the validity of the condition (the reliability of the condition), fresh theories based on the Imamayeh fiqh and the civil code of Iran has been focused as the inclusion of the condition within a contract in the principal conditions (generally or in some titles) has followed the general rules of the contracts.